Interpol and its role in combating international terrorism - Hussain Saeed Al-Ghafri,; Yousef bin Saeed Al-Kalbani, (International Journal of Law Research and Studies, 2026)
This research examines international policies adopted to combat global terrorism, focusing on the pivotal role of the International Criminal Police Organization (INTERPOL) in addressing transnational terrorist crimes. The study explores the evolution of international terrorism and its political, legal, and social dimensions, while analyzing the legal framework governing INTERPOL’s operations and its mechanisms for information exchange and coordination among member states. It further discusses the organization’s cooperation with the United Nations and regional bodies in countering terrorism and organized crime, highlighting major technical, legal, and political challenges that hinder its effectiveness. The research concludes that combating terrorism requires an integrated international approach that balances state sovereignty with enhanced global security cooperation, alongside the development of advanced technological and legislative tools to strengthen INTERPOL’s capacity in addressing emerging terrorist threats.
Keywords: International Terrorism; INTERPOL; International Cooperation; Organized Crime; Global Security; Counterterrorism; Security Policies